Inheritance or contagion? Postures on the transmission of tuberculosis in Costa Rica - Rojas Madrigal, Monserrat (2019)
It shows the controversy raised by the medical authorities during the year 1934, about the way of transmission of tuberculosis. For this, the different positions of some physicians interested in the subject during that time are analyzed, which, based on their work experiences with patients suffering from phthisis, write in the medical journal of Costa Rica or opinions both in the medical assembly and in the second medical congress celebrated in the country during that same year, about the forms of contagion of tuberculosis in the Costa Rican population. Received: 01-13-2019 Approved: 03-29-2019